Patient satisfaction in outreach dental programs of a Dental Teaching Hospital in Modinagar (India) - Vaibhav Vashishtha; Basavaraj Patthi; Ashish Singla; Ritu Gupta; Ravneet Malhi; Venisha Pandita (Wolters Kluwer Medknow Publications, 2015)
Introduction: Patient satisfaction with dental services has received minimal attention in India. The perceptions of satisfaction of the oral health care service among patients in outreach dental programs and their level of satisfaction are an important factor toward improving the service provided. Aim: To assess patient satisfaction at outreach dental programs of a Dental Teaching Hospital in Modinagar India. Materials and Methods: A cross-sectional study was conducted among patients attending community dental outreach programs organized by the Dental Teaching Hospital over a period of 1-month. A total of 4 weekly and 1 monthly camp were included, and all the subjects who attended these camps were administered the pretested structured questionnaire. The questions were related to the satisfaction level of the patient in outreach dental camps and answers were recorded using a four-point "Likert" scale with Chi-square and independent t-test were used for statistical analysis. Results: The results showed that level of satisfaction among patients were higher in weekly camps (95.2%) as compared to monthly camps that is (80%). The response rate for the weekly camps was 95.2%, whereas for the monthly camp was 80%. Overall patient satisfaction scores with the care received ranged from the poor (1) to excellent (4). The highest reported levels of satisfaction were for the aspects of explanation of dental treatment by the doctor followed by meeting of perceived need of the patient with the treatment. Conclusion: Patient satisfaction with the community dental outreach programs was high, reflecting the delivery of quality treatment and positive attitude of the dental team during the camps. The overall high level of patient satisfaction reflected the dental team's approach of responsibility and accountability toward the target population.